ChemInform Abstract: Kinetic Resolution of Racemic Mandelic Acid Esters by N, N′‐Dioxide‐Scandium‐Complex‐Catalyzed Enantiomer‐Selective Acylation. Issue 17 (April 2015) - Zhang, Yuheng; Liu, Xiaohua; Zhou, Lin; Wu, Wangbin; Huang, Tianyu; Liao, Yuting; Lin, Lili; Feng, Xiaoming
Abstract A simple and efficient acylative kinetic resolution of racemic mandelic acid esters is accomplished with a chiral N, N‐dioxide‐scandium(III) complex under mild and base‐free reaction conditions.